2019
DOI: 10.1523/eneuro.0046-19.2019
|View full text |Cite
|
Sign up to set email alerts
|

Functional AssessmentIn Vivoof the Mouse Homolog of the Human Ala-9-Ser NHE6 Variant

Abstract: Christianson syndrome (CS) is an X-linked neurogenetic disorder resulting from loss-of-function (LoF) mutations in SLC9A6, which encodes the endosomal Na+/H+ exchanger 6 (NHE6). NHE6 regulates proton efflux from endosomes and, thus, participates in regulating cargo processing and trafficking. LoF mutations in NHE6 cause aberrant acidification of endosomes. While CS arises in males generally due to clear LoF mutations, other potentially hypomorphic variants have emerged, yet most of these variants have not been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…Although this experimental cell system has proven informative in deciphering NHE6 function, we cannot exclude the possibility that any deleterious consequences of the A9S and R568Q variants may be more subtle and manifested only in certain neuronal cell-types. However, during the preparation of this manuscript, Ouyang and co-workers (88) reported that mice genetically manipulated by CRISPR/Cas9 technology to harbor the homologous human NHE6 A9S variant (i.e., mouse A11S) appeared normal in terms of brain morphology, NHE6 subcellular localization and intra-endosomal pH of hippocampal neurons. Though a behavioural assessment of these mice was not described, we envision that human A9S and possibly the R568Q variants are likely benign and possibly misattributed as the cause of the patients' neurological symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Although this experimental cell system has proven informative in deciphering NHE6 function, we cannot exclude the possibility that any deleterious consequences of the A9S and R568Q variants may be more subtle and manifested only in certain neuronal cell-types. However, during the preparation of this manuscript, Ouyang and co-workers (88) reported that mice genetically manipulated by CRISPR/Cas9 technology to harbor the homologous human NHE6 A9S variant (i.e., mouse A11S) appeared normal in terms of brain morphology, NHE6 subcellular localization and intra-endosomal pH of hippocampal neurons. Though a behavioural assessment of these mice was not described, we envision that human A9S and possibly the R568Q variants are likely benign and possibly misattributed as the cause of the patients' neurological symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Samples containing 20 µg of protein were then boiled in sample buffer at 95 °C for 5 min before loading onto a 4-12% SDS-PAGE gel (Novex #NP0321Box). Following separation of proteins by electrophoresis, the gel was transferred to a nitrocellulose membrane (Novex #LC2000), and Western blot was performed using standard procedures (Ouyang et al, 2019; Xu et al, 2017). The Western blot was analyzed with the Li-CoR Odyssey Imaging System.…”
Section: Methodsmentioning
confidence: 99%
“…Following separation of proteins by electrophoresis, gels were transferred to nitrocellulose membranes (Novex #LC2000). Western blots were performed using standard procedures (Lizarraga et al, 2021; Ouyang et al, 2019; Xu et al, 2017) and were analyzed with the Li-CoR Odyssey Imaging System. Proteins were detected using rabbit anti-NHE6 antibody (1:1,000 working dilution; Covance #048) (Ouyang et al, 2013) and mouse anti-α-Tubulin (1:5,000 working dilution; Sigma #T6074).…”
Section: Methodsmentioning
confidence: 99%